2015
DOI: 10.1038/ncomms6846
|View full text |Cite
|
Sign up to set email alerts
|

Filopodia-based Wnt transport during vertebrate tissue patterning

Abstract: Paracrine Wnt/b-catenin signalling is important during developmental processes, tissue regeneration and stem cell regulation. Wnt proteins are morphogens, which form concentration gradients across responsive tissues. Little is known about the transport mechanism for these lipid-modified signalling proteins in vertebrates. Here we show that Wnt8a is transported on actin-based filopodia to contact responding cells and activate signalling during neural plate formation in zebrafish. Cdc42/N-Wasp regulates the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
289
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 221 publications
(314 citation statements)
references
References 74 publications
14
289
1
Order By: Relevance
“…Consequently, we investigated whether sFRP2 or Ror2 have an effect on Fz7 localization and internalization. High-resolution in vivo imaging in zebrafish embryos has recently proven to be a valuable tool to study trafficking of Wnt ligands and receptors in a living vertebrate model organism (46,47). By using this imaging-based in vivo approach, we observed that, in the absence of Wnt5a, Fz7 is localized at the cell membrane as well as in intracellular vesicles.…”
Section: Sfrp2 Modulates Non-canonical Wnt Signalingmentioning
confidence: 78%
“…Consequently, we investigated whether sFRP2 or Ror2 have an effect on Fz7 localization and internalization. High-resolution in vivo imaging in zebrafish embryos has recently proven to be a valuable tool to study trafficking of Wnt ligands and receptors in a living vertebrate model organism (46,47). By using this imaging-based in vivo approach, we observed that, in the absence of Wnt5a, Fz7 is localized at the cell membrane as well as in intracellular vesicles.…”
Section: Sfrp2 Modulates Non-canonical Wnt Signalingmentioning
confidence: 78%
“…We were able to show that Wnt8a accumulates on the plasma membranes of Wnt-producing cells (Stanganello et al, 2015). These Wnt8a clusters recruit the transducer of Cdc42 -dependent actin assembly protein 1 (Toca-1; also known as fnbp1l), which determines the positions of new filopodia by locally activating the filopodia nucleation complex (Ho et al, 2004).…”
Section: Wnt Cytonemes In Developmentmentioning
confidence: 93%
“…Recent data suggest that Wnt proteins are distributed on long signaling filopodia known as cytonemes, which allow contactdependent, juxtacrine signaling over a considerable distance. We have recently shown that, in zebrafish, Wnt8a is transported on actin-containing cytonemes to cells, where it activates the signaling required for the specification of neural plate cells (Stanganello et al, 2015). Concomitantly, the Wnt receptor Frz was identified on cytonemes to enable the retrograde transport of Wnt proteins on these protrusions during flight muscle formation in Drosophila (Huang and Kornberg, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The cells of the brain midline, along with those of the mid-diencephalic and midhindbrain boundaries, represent the signaling glia, which is a source of secreted factors including Wnts involved in the dorsoventral and antero-posterior specification of the brain (Jessell, 2000;Korzh et al, 2007). The signaling glia, which possess extended soma and/or filopodia, function as a conduit of distant delivery of hydrophobic Wnts (Kondrychyn et al, 2013;Korzh, 2014;Stanganello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%